In Search of Quality Human Resources in Education: Professional Competency, Compensation, Working Climate, and Motivation toward Vocational Teachers' Performance - Muazza Muazza (Indonesian Research Journal in Education |IRJE|, 2021)
This study aimed to find out the effect of professional competency, compensation, working climate, and motivation on the performance of vocational teachers in Muaro Jambi Regency. The data were collected through an empirically validated questionnaire from 212 respondents. The variables consisted of professional teacher competency (X1), compensation (X2), and working climate (X3), and one moderator variable; motivation (Y), and one bound variable; teacher performance (Z). Descriptive and inferential analysis technique was used to analyze the data through SPSS and Smart PLS 3.2.7 applications. The results of descriptive analysis illustrated that teacher performance, teacher professional competency, working climate and working motivation in the very high category. At the same time, compensation fell into the good category. The statistical analysis results revealed that teacher professional competency, compensation, and working climate affected teacher working motivation, while professional teacher competency, working climate, and motivation involved teacher performance. Compensation was predicted not to affect teacher performance where P-Value 0.810 was greater than 0.05. Teacher professional competency, compensation, and working climate affected teacher performance through motivation as moderator variables to teacher performance. Professional teacher competency, compensation, and working climate were predicted to have a simultaneous effect on teacher working motivation. Professional teacher competency, compensation, working climate, and motivation were predicted to have a simultaneous effect on teacher performance. It is recommended that vocational school teachers in Muaro Jambi regency improve their performance for better student learning achievement.